THE LEADERSHIP INFLUENCE AND SELF EFFICACY ON MOTIVATION - Albantani, Sukro Muhab (Journal of Education Research in Administration and Management (JERAM), 2017)
The purpose of this research is to determine the influence of school leadership by the principal and self-efficacy towards the teachers’ motivation. This research used expost facto method, by involving 165 Natural Science teacher of integrated Islamic school as a randomly selected sample. The results of this research indicates that there are significantly differences in motivation of the Natural Science teachers between teachers led by principals who have a transformational leadership with transactional leadership. There is also a significant interaction impact between principal's leadership and self-efficacy on the teachers’ motivation.